Perpolitikan Indonesia Pasca Pilpres dan Relevansi Teori Politik Al-Ghazali - Mawar Febrianti (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
Indonesia experienced a great political upheaval after the implementation of the April 14 2019 presidential election yesterday. Such a situation is the culmination of a feeling of dissatisfaction from the part of the Indonesian people towards the government that has been going on so far and for the implementation of the 2019 presidential election which is considered incompatible with the presidential election's honesty (honest and fair). For this reason, Indonesia, in this case the government and the people, must immediately rise up, and control the condition of Indonesian politics to immediately return to conducive conditions. Al-Ghazali's political theory emphasizes the importance of choosing leaders who have good aqeedah and adab, are intelligent, master the knowledge of religion and government, are fair, understand the difficulties of the people, are close to the people. The leader must also be close and willing to listen to the advice of the scholars (religious leaders, national figures and intellectuals), not accepting bribes or bribing and not corruption. The implications of al-Ghazali's theory are very possible and quite relevant to be implemented in Indonesia, but of course it must be adapted to the system of government, culture and society in Indonesia.